ChemInform Abstract: Novel Spirooxindole—Pyrrolidine Compounds: Synthesis, Anticancer and Molecular Docking Studies. Issue 33 (19th August 2014) - Arun, Y.; Saranraj, K.; Balachandran, C.; Perumal, P. T.
Abstract A variety of novel spirooxindole‐pyrrolidine derivatives are synthesized by 1, 3‐dipolar cycloaddition reactions of azomethine ylides derived from isatin and sarcosine or thiaproline with acrylonitriles (I).